The Real and Imaginary Volume Integrals in Spherical-Statistical Optical Potential of Neutron scattering from 56Fe nuclei - Abd Ali, Fatimah Fadhil; Jasim, Mahdi Hadi (Iraqi Journal of Science, 2018)
A spherical-statistical optical model (SOM) has been used to calculate and evaluate the neutron interaction with medium nuclei (40 ). Empirical formulae of the optical potentials parameters are predicted with minimize accuracy compared with experimental bench work data. With these optical formulae an evaluation of the shape and compound elastic scattering cross-section of interaction neutrons with 56Fe nuclei at different energy range (1-20) MeV has been calculated and compared with experimental results. Also, volume integrals for real and imaginary potential energies have been evaluated and matched with the standard ABAREX code. Good agreements with have been achieved with the available experimental data.